ENHANCING VOCATIONAL STUDENTS’ CREATIVITY THROUGH LETTER MOLD-ASSISTED FRUITS AND VEGETABLES CARVING PRACTICE: A QUALITATIVE CASE STUDY IN INDONESIAN CULINARY EDUCATION - Hertina Arianesia; Nunung Nurjanah; Yoto Yoto (SOSIOEDUKASI, 2026)
Creativity is one of the main competencies that needs to be developed in vocational education, particularly in the culinary field which demands both technical and aesthetic ability. However, empirical studies on the use of structured learning media to support the development of student creativity in fruits and vegetables carving practice are still relatively limited. This study aims to analyze the dimensions of student creativity in fruits and vegetables carving practice using letter mold media at SMK Negeri 3 Blitar. The study used a qualitative approach with a single case study design. Data were collected through semi-structured interviews with the head of the culinary study program, teachers, and students, supported by observation and document analysis. Data analysis was conducted using the interactive model of Miles and Huberman, while data validity was ensured through source, technique, and time triangulation. The results showed five dimensions of creativity developing in students, namely originality in generating carving design ideas, technical creativity in modifying the use of letter molds, aesthetic creativity in the visual quality of carving results, symbolic creativity in conveying themes through the work, as well as various contextual challenges such as limitations of time, equipment, and differences in student ability that affect the creative process. These findings show that letter mold media can facilitate student creativity as a flexible and guided learning tool. The results of this study have implications for the development of innovative learning strategies and the design of vocational education curricula in the culinary field oriented toward strengthening creativity.